A study on the effect of nami extract (Dioscorea hispida Dennst.) on golden apple snails (Pomacea canaliculata L) - Dionela, Josephine C. (Animo Repository, 1994)
Freeze dried and oven dried nami extracts of nami tuber (Discorea hispida Dennst.) in the series of 7g/l, 6g/l, 5g/l, 3g/l, 2g/l concentrations are used to find out their effect on the mortality of golden apple snails at six different age levels, namely: 0 week, 1 week, 2 weeks, 3 weeks, 4 weeks and 8 weeks. Observed responses of treated golden apple snails include avoidance reactions, mucus secretions and mortalities. Analysis of the mortality data after a 24-hour toxicity test showed that the levels of concentration of nami extract significantly affect the mortality of golden apple snails. It was found that the higher the concentration of nami extract, the higher is the percent mortality. However, various age groups of golden apple snails did not show any significant difference in their avoidance reaction to nami extract. There was also no significant difference observed between freeze-dried and oven-dried nami extracts in terms of their effects on snail mortality. Furthermore, no significant interaction was observed in the form of preparation and concentration of nami extract and also on form of preparation of nami extract and age of the golden apple snails. However, LC 50 at 4.26g/l nami extract regardless of form of preparation was obtained in the experiment. It is concluded that nami extract can be a potential botanical molluscicide against golden apple snail.